2018
DOI: 10.1088/1555-6611/aab451
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photodetectors based on reduced graphene oxide nanoparticles and graphene oxide

Abstract: Two photodiode (PD) designs incorporating graphene oxide (GO) and reduced graphene oxide (rGO) are proposed and fabricated. Both PDs have 50 mm thick silver electrodes deposited on the active area, and another electrode consisting of either GO or rGO nanoparticles (NPs). The GO and rGO NPs are deposited onto the p-type silicon substrate by the drop casting method. Both fabricated PDs show good sensitivity and quick responses under 974 nm laser illumination at 150 mW. The photoresponsivity values and external q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Figure shows the photoconductive ON/OFF switching response of both WS 2 -QDs/RGO and RGO sensor having an identical channel length of 8 mm at constant power (1.4 mW mm –2 ) for various illumination wavelengths, i.e., 405, 635, and 1064 nm. The bare RGO sensor is studied here as a reference sensor, solely to identify and quantify its contribution in the WS 2 -QDs/RGO sensor since RGO itself is a good photoconductive material as reported by many authors. , The photoresponse shows a sharp increase in photocurrent in both the sensors during light exposure, which is attributed to the collection of excess photogenerated carriers across the electrode terminals over the base level (or dark current response). Multiple ON/OFF cycles show persistent photoresponse profiles with good cyclic repetition, a crucial characteristic of the detector to determine its suitability for long-term application.…”
Section: Photodetection Performance Of the Developed Sensormentioning
confidence: 99%
“…Figure shows the photoconductive ON/OFF switching response of both WS 2 -QDs/RGO and RGO sensor having an identical channel length of 8 mm at constant power (1.4 mW mm –2 ) for various illumination wavelengths, i.e., 405, 635, and 1064 nm. The bare RGO sensor is studied here as a reference sensor, solely to identify and quantify its contribution in the WS 2 -QDs/RGO sensor since RGO itself is a good photoconductive material as reported by many authors. , The photoresponse shows a sharp increase in photocurrent in both the sensors during light exposure, which is attributed to the collection of excess photogenerated carriers across the electrode terminals over the base level (or dark current response). Multiple ON/OFF cycles show persistent photoresponse profiles with good cyclic repetition, a crucial characteristic of the detector to determine its suitability for long-term application.…”
Section: Photodetection Performance Of the Developed Sensormentioning
confidence: 99%
“…The value of photosensitivity is greater than that observed in other novel photosensing devices. , If the total area of the device is considered, the photoresponsivity is calculated to be 3.55 A/W. The photoresponsivity of rGO-Si devices is significantly larger than the previously reported values in novel photosensing devices and graphene-based sensors. , ,, The rGO structures have also been grown on Si substrates to fabricate graphene-based photosensors. , In all of the above cases, the nanostructuring of Si was not utilized. In the present work, we have shown that by nanostructuring Si, we have formed a direct band gap (in Si) which improves its optoelectronic properties.…”
Section: Results and Discussionmentioning
confidence: 91%
“…40,41 If the total area of the device is considered, the photoresponsivity is calculated to be 3.55 A/ W. The photoresponsivity of rGO-Si devices is significantly larger than the previously reported values in novel photosensing devices and graphene-based sensors. 5,[37][38][39][40]42,43 The rGO structures have also been grown on Si substrates to fabricate graphene-based photosensors. 3,44 In all of the above cases, the nanostructuring of Si was not utilized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The EDX spectral analysis revealed the atomic percentage of the atomic oxygen present in G-rGO (19.90%) and GO (40.45%) (Table ). Because oxygen-carrying functional groups had been removed from the surface of GO, the oxygen atomic % had decreased …”
Section: Resultsmentioning
confidence: 99%